KORELASI KEMAMPUAN KOGNITIF PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN SIKAP KEAGAMAAN SISWA KELAS VII SMP SUNAN GIRI 1 LAMONGAN - Mumtahanah, Nurotun; Taufik, Mochamad (Akademika, 2018)
Based on the results of observations and theoretical studies that researchers found, that cognitive ability is very important in controlling affective and psychomotoric areas. While religious attitude is the internalization of the appreciation and understanding of students in studying Islamic religious education. Subjects in this study were all students of class VII SMP Sunan Giri 1 Lamongan academic year which amounted to 19 students. Methods of data collection using observation method, interview method, method of quisioner, and method of documentation. After the data collected then analyze the data by using the formula Mean, Percentage and Product Moment. From the results of this study can be seen that the implementation of cognitive abilities in Islamic education lessons in Junior High School Sunan Giri 1 Lamongan quite well, with an average of each student get the value of report card 95 based on the calculation using the formula mean (average). The religious attitudes of the seventh grade students of Junior High School Sunan Giri 1 Lamongan are categorized as good enough, based on the result of data analysis using the percentage formula obtained result 53.68% which then the result is matched with the measurement standard is in the range 40% - 55% good enough and the correlation between cognitive ability in the subjects of Islamic Education with the religious attitudes of students of class VII SMP Sunan Giri 1 Lamongan, this can be proven from the product moment calculation 0,552 from 5% significant level with the number 0,482 on the number of respondents (N) 17. This becomes the rest of the conclusion that the working hypothesis (Ha) is accepted and the null hypothesis Ho is rejected, since rh = 0.552 proves to be greater than rt = 0.482 at the 5% significance level. And if 0.552 is consulted on the interpretation table is between the intervals of 0.400- 0.600 which means the correlation level is moderate or sufficient.